Investigation of acute diarrhoea outbreak at Narasapura, Kolar - ., Vishwas; ., Ravishankar (International Journal Of Community Medicine And Public Health, 2019)
Background: Greatest risk of acute diarrhea outbreaks occurs in over-populated communities & refugee settings characterized by poor sanitation, unsafe drinking-water and increased person to person transmission. Because the incubation period is very short, number of cases can rise extremely quickly and it calls for a prompt and thorough investigation. There were reports of cases of acute diarrhoea and based on the preliminary field work, the existence of an outbreak was confirmed. Hence it was decided to investigate the outbreak with objectives to determine the causes and source of acute diarrhoea outbreak at Narasapura village in Kolar and to suggest control measures. Methods: The cross sectional study was conducted in Narasapura village of Kolar which is a fast growing industrial area. All the households and migratory settlements of the affected area were included. Attack rates of the disease were computed, epidemic curve drawn and the results were analyzed to draw conclusions. Control measures were applied simultaneously. Results: The diarrhoea attack rate at AD colony was 10%. Males (65%) were more affected compared to females (35%). 15.4% stool samples were positive for Vibrio cholera and 18% of the water samples was found to be non-portable. Vibrio cholerae O1 biotype El Tor serotype Ogawa strain was implicated as the cause for present outbreak. Conclusions: Cholera continues to be a public health problem in migratory settings, causing disease outbreaks. Environmental risk factors and lack of awareness are the contributory factors which need to be addressed.